Liberdade e vontade na filosofia moral Kantiana - Lima, Geane Vidal de Negreiros (2012)
This dissertation intends to analyze the notions of freedom and desire in Kant's moral philosophy. The philosopher defends the institution of a universal principle, capable of limiting human impulses, since, in virtue of natural necessity, the subject is not strong enough to escape the traps of the inclinations. Kant proposes to the moral a pure practical reason, which enables the application of theory to practice in the role of freedom of the transcendental subject of think and act. The autonomous subject, by the relationship between good will and freedom, creates its own laws, while respects it and obeys mandatory under the duty (Solen), which is a priori concept, as a fact of reason. The reason is therefore responsible for the moral assumptions that are: freedom, immortality and God, ideas that represent the supreme good, and by the imperatives, determine moral action. Another perspective of this study extends the exposure of the consequences of Kant's philosophy and the criticism of modern and contemporary thinkers to his thought, which proposals appear for a new concept of morality that answer current issues of society.